Work hours and the risk of hypertension: the case of Indonesia - Friska Aulia Dewi Andini; Adiatma Y. M. Siregar (BMC, 2024)
Abstract Background Individuals working excessive hours is a worldwide phenomenon. In Indonesia, over 32 million people work more than 40 h per week, contributing to around 26% of the workforce. Excessive working may affect health, increasing the risk of cardiovascular diseases such as hypertension. Hypertension affected around 34% of Indonesian adults, approximately 63.3 million people and led to about 427,000 deaths in 2018, and the prevalence remains high at 29.2% in 2023. This study aims to analyze the relationship between work hours and the risk of hypertension among working individuals in Indonesia. Methods This study used a pooled cross-sectional data from the Indonesian Family Life Survey (IFLS) wave 4 (2007) and wave 5 (2014) and performed a logit regression analysis to examine the likelihood of a working individual having hypertension based on the individual's work hours. A dummy variable of hypertension is created based on the result of blood pressure measurement. The sample consists of 22,500 working individuals in Indonesia. This study controlled for job characteristics, sociodemographic status and health-behavioral risk factors such as BMI and smoking behavior, and performed additional regression analyses for alternative models to check for robustness. Results Our findings showed that there is a higher probability of having hypertension for workers who work longer hours by 0.06% points for each additional hour of work (p < 0.01). Other factors such as physical activity and smoking behavior have also been demonstrated to be significantly correlated to the risk of hypertension. Conclusions This study revealed a positive relationship between work hours and hypertension. Although this study cannot suggest causality, the strongly significant correlation may provide an idea and an overview regarding the risk of hypertension among working individuals in Indonesia. The Indonesian government could consider conducting further studies to implement and promote flexible working arrangements initiatives and incentive programs to improve workers' health outcomes.